In vivo recovery and long-term effect of phosalone in Oreochromis mossambicus (Peters) - Siva Parvathi, M Leela; Reddy, D Chandra Sekhara (Indian Journal of Fisheries, 2011)
Two different size groups (1.0 g and 6.0 g) of Oreochromis mossambicus (Peters)were selected and each size group divided into three subgroups. The first subgroupof fish (both size groups) were maintained in normal uncontaminated tapwater until they attained a body size of 12.0 + 0.05 g (control group). The secondsubgroup (of each size group) was exposed for 150 (time required for 1.0 g O.mossambicus to attain 12.0 + 0.05 g of body weight) and 60 days (time requiredfor 6.0 g O. mossambicus to attain 12.0 + 0.05 g of body weight) to a daily sublethalconcentration (1/10th LC50) of phosalone which forms the long term exposedgroup. The third subgroup (each size group) returned to normal uncontaminatedwater following 7 day exposure to a daily sublethal concentration ofphosalone (short-term exposed) and maintained until they attained 12.0 + 0.05g of body weight (recovery group). Total anthrone positive substances (TAPS)and glycogen (Gly) content of liver, muscle and gill were measured. Both sizegroups of control fish exhibited a positive correlation between total anthronepositive substances and glycogen. Statistically significant difference was foundbetween control vs long-term and short-term exposed fishes (both size groups).In this third subgroup, total anthrone positive substances and glycogen weredecreased but showed recovery after returning to uncontaminated waters.Phosalone effect was more marked in liver than muscle and gill. Early recoveryin gill from phosalone stress was noticed in both sizes of fish.